IRON DEFICIENCY ANEMIA IN SCHOOL-AGE CHILDREN, OPTIMIZATION OF PREVENTION AND CORRECTION OF TREATMENT - Atajanova Shaira Khalilovna (Scholar Express Journals, 2024)
Currently, the relevance of the problem of early diagnosis and adequate treatment of IDA in children is beyond doubt, since iron is involved in many vital processes: in redox and enzymatic reactions, hematopoiesis, supply of organs and tissues with oxygen. Iron deficiency can cause stunted growth and development in children, reduce performance, and contribute to an increase in the incidence of acute respiratory diseases. Early diagnosis, adequate therapy and prevention of IDA are the main components of a modern comprehensive approach to the treatment of anemia to ensure the health of children
Keywords: iron deficiency anemia; iron-containing drugs; iron bioavailability